Aktivitas Public Relations Pengelola Situs Pariwisata Tanjung Lesung Untuk Meningkatkan Jumlah Wisatawan - Ayu Wahyuni Solihah; I Nyoman Musiasa; Mohammad Shihab (Jurnal Komunikasi Global, 2018)
The tourism sector is one of the sectors to increase the economy of the state. Banten is one of the province in Indonesia that has the potential to develop the tourism sector since Banten has Tanjung Lesung as Special Economic  Zone. PT Banten West Java Tourism Development (BWJTD) as a developer of Tanjung Lesung has to manage various strategies to increase the number of tourists. This study explained the public relation strategies of PT BWJTD to increase the number of tourists to Tanjung Lesung. It used a model of strategic planning for public relations from Ronald D. Smith for analysis, known as The Nine Steps of Strategic Public Relations.  The model includes research formative, strategy, tactics, and evaluation. The data were collected using in-depth interviews with three key informants, observation on tactics, and documentation related to Tanjung Lesung. Based on the findings, it can be concluded that the public relation strategies used by PT BWJTD are the proactive strategies.